Millennials' Response Toward Luxury Fashion Brands: The Balance Theory’s Perspective - Hasnizam Shaari; Siti Nadia Sheikh Abdul Hamid; Hashed Ahmed Mabkhot (Gadjah Mada International Journal of Business, 2022)
The mushrooming growth of luxury brands has been evidenced worldwide, especially among developing countries such as Malaysia. Despite Malaysian consumer confidence slowing due to uncertainty about the economic conditions, the demand for luxury brands is still expected to rise. Interestingly, a significant rise in the demand for luxury brands has been observed in the millennials group. This study examines the relationship of electronic word-of-mouth and the country of origin’s image on millennials' attitudes toward luxury brands and the intention to purchase luxury fashion brands. The study among 333 millennials revealed that the country of origin’s image has both direct and indirect effects on the intention to purchase luxury fashion brands. Electronic word-of-mouth (eWOM) was found statistically insignificant in explaining the intention to purchase, but eWOM had a significant relationship on intention to purchase through its mediation effect of the attitude toward luxury brands. Accordingly, the findings found support for the balance theory. The results also suggest that the owners of luxury brands should carefully manage the country of origin because it will affect the overall brand image, as perceived by consumers. Limitations and future directions of the study are also included at the end of the article.